Mathematical Model of Groundwater Flow in Safwan Al - Zubair Area, South of Iraq - Aboodi, Ali H. Al; Kadhimi, Ahmad M. Al; Tai, Majeed A. Al (Basrah Journal for Engineering Sciences, 2010)
A two-dimensional mathematical model has been constructed by using finite difference method for representation the groundwater flow in both steady and unsteady states at the upper aquifer of Dibdibba formation. The hydraulic characteristics of this aquifer have been redistributed based on observed data for the period (1988• l 989). A verification test is added to check the model correctness by matching the calculoted levels with the ones observed for the year 2000.A model was set to predict the groundwater levels up to the year 2010. Results of prediction show a reduction in groundwater level about (Im) in the central parts of the study area compared to the level of this groundwater in the year 2000.0n the other hand, this decrease is reaches (0.5m) in the western parts of this area.